PENINGKATAN KOMPETENSI PEDAGOGIK DALAM PEMBELAJARAN DARING MASA PANDEMI COVID 19 MELALUI PENERAPAN SUPERVISI KLINIS PADA GURU - Anggraini, M. L. Dyah K. (Jurnal Inovasi Pembelajaran di Sekolah, 2021)
Improving Pedagogic Competence in Online Learning During the Covid 19 Pandemic Period Through the Application of Clinical Supervision on Teachers at SD Negeri Krapyak, West Semarang District, Semarang City Semester 2 Year 2020/2021. This study aims to determine the effect of applying clinical supervision of online learning during the Covid 19 Pandemic on KRAPYAK State Elementary School teachers. This research was conducted for 4 Months of Semester II of the 2020/2021 academic year from the preparation of the proposal to the writing of the research report in December 2020 to April 2021. The subjects of the study were all class teachers of SD Negeri Krapyak. The method is a way to simplify the way research works and is a determining factor for the success of a study. The method used is school action research with two cycles of action. Each cycle consists of four stages, namely planning, taking action, observing, and reflecting. Analysis of the data used in this study using comparative descriptive analysis, namely by comparing the results of the initial test, the first cycle, and the second cycle. The researcher concluded that the application of clinical supervision of online learning during the Covid 19 pandemic for teachers at SD Negeri Krapyak, West Semarang District, Semarang City in 2020/2021 greatly influenced the improvement of teachers' pedagogic competence. The results of the supervision of the initial conditions of teacher pedagogic competence obtained an average value of 3.0 (1.17%) while in the first cycle the average value of pedagogic competence was 3.5, an increase of 0.5 from the initial conditions, and in the second cycle the average value was 3.9, an increase of 0.4 from the results. previous cycle.